Working Dogs Drinking a Nutrient-Enriched Water Maintain Cooler Body Temperature and Improved Pulse Rate Recovery After Exercise - Zanghi, Brian M.; Robbins, Patrick J.; Ramos, Meghan T.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2018)
Exercise-related physiological changes were evaluated in hydrated, exercise-conditioned working dogs with free access to tap water (TW) with or without a nutrient-enriched water supplement (NW). Physiological samples and measures were collected before and after work-related field tasks in a warm and moderately humid ambient environment. In a cross-over design study, 12 dogs (age range 8-23 months) were evaluated on 3 separate occasions within each period with exercise bouts up to 30 min, on days -4, 3, and 11. Dogs were offered either ad libitum TW or portion-controlled NW daily plus ad libitum TW. Prior to and serially after exercise, pulse rate (PR), core (BTcore) and ear (BTear) temperature were recorded. Urine was collected first thing in the morning, whereas blood samples collected and body weight (BW) recorded pre- and immediately post exercise. Ambient temperature was above 21.7oC (71oF) and relative humidity ranged from 36% to 76%. Activity parameters, AM urine measures, post-exercise percent change of BW, resting PR and resting BTcore did not differ between treatment groups on any exercise day. At the completion of exercise, mean BTcore for all dogs ranged from 104.8 to 105.6oF. Immediate post-exercise BTear was always lower compared to BTcore and means ranged from 103.3 to 104.0oF. The effect of time was highly significant (P < 0.001) for both BT measures with both BTcore and BTear recovering to resting levels by 60 min post exercise. PR and several blood values showed a significant main effect of time. Over the recovery period, dogs in the NW group had lower mean BTear and PR by 0.6oF and 3.4 bpm, respectively. Daily ingestion of a NW in combination with free access to TW can reduce the post-exercise-related BTcore and BTear hyperthermia, and improve pulse rate recovery following exercise in this population of working dogs undergoing 30 min bout of exercise.